France : Report on Observance of Standards and Codes- Fiscal Transparency and Data Module Updates. (IMF Staff Country Reports; Country Report ;, 2004)
These updates to the Report on the Observance of Standards and Codes on Fiscal Transparency and Data Module on France highlight the transparency of budget preparation. The report includes a four-year projection of revenue, expenditure, and balance for the various components of the general government expressed under national accounting conventions. The metadata and summary methodologies underlying the economic statistics are being regularly updated on the Dissemination Standards Bulletin Board (DSBB). The possibility of developing a module for detecting anomalous price shifts in the new automatic price collection system is explored.